Workshop on Fostering an Entrepreneurial Spirit Among Young Generations in the Bonsai Thematic Village, Tangerang - Winanti; Supiana, Nana; Ligawati; Waruwu, Hatoli; Iskandar, Joni; Basuki, Sucipto; Maqin, Samsul; Kamar, Karnawi; Alfariz, Kadira Hilman; Yusuf (Institut Teknologi dan Bisnis Asia Malang, 2024)
Purpose: This research paper aims to address the lack of employment and skills among young members of Karang Taruna in the Bonsai thematic village. It explores the potential for entrepreneurship to enhance their standard of living and contributes to youth empowerment within rural communities.Method: A qualitative research design was employed, utilizing workshops as the primary data collection method. Participants included Karang Taruna members and teenagers from the Bonsai village. The workshops focused on interactive learning about entrepreneurship, with data collected through participant feedback and observations.Practical Applications: The findings emphasize the practical benefits of entrepreneurial education, which can reduce idle time and foster economic activity. Skills acquired can lead to increased engagement in the bonsai business and other ventures, improving economic prospects for local youth.Conclusion: This study highlights the need for entrepreneurial education to combat youth unemployment in the Bonsai thematic village. The workshop serves as an effective intervention, demonstrating how targeted education can empower communities and improve livelihoods.